Understanding Girls' Motivation to Participate in Sport: The Effects of Social Identity and Physical Self-Concept - Murray, Ross M.; Koulanova, Alyona; Sabiston, Catherine M. (Frontiers in Sports and Active Living, 2022)
Introduction: Girls are often less motivated to participate in community sport compared to boys. Having a strong social identity with a sports team is positively associated with motivation to continue participation in sport, yet the mechanisms explaining this association are not well-known. In the current study, physical self-concept is tested as a mediator of the association between social identity and motivation. Method: Girl badminton athletes were recruited to examine how the team environment shapes physical self-concept, and whether this association relates to motivation to participate in sport. Ninety-five girls completed a self-report survey to measure social identity, physical self-perceptions, and motivation. Two mediation models were conducted to examine whether physical self-concept mediated the relationship between social identity and autonomous motivation and controlled motivation. Results: Physical self-concept partially mediated the relationship between social identity and autonomous motivation. The bootstrapped unstandardized indirect effect was, b =.05, 95% CI = .002 to .14. Physical self-concept fully mediated the relationship between social identity and controlled motivation. The bootstrapped unstandardized indirect effect was, b = -0.13, 95% CI = -0.30 to -.01, p = .04. Discussion: These results highlight the importance of the group context in relation to individual physical self-concept and motivation. Overall, targeting aspects of the team environment in community-level sport may be an important strategy to improve girls’ physical self-concept, and autonomous motivation to continue sport participation.